Sistem Presensi Mahasiswa Dengan Fingerprint Berbasis Website - Wijayanto, Eko; , Yusuf Sulistyo Nugroho., S.T., M.Eng (2017)
Today, the development of information technology is increasingly rapidly. Not least in the academic field. One use of technology in the field of student academic is attendance system. In Indonesia, there's also a college that still use attendance retrieval by conventional methods. In this paper, to solve the problem the authors proposed a system of student presence with finger print-based website. Presence fingerprint system aims to save time during the process of making attendance. In addition, the system will reduce the level of student fraud related to the presence of students. In this system, students will only be asked to upload the image fingerprints to mark the presence of students. This system development using the waterfall method which involves the integration of a variety of web-based open source technologies such as MySQL, PHP and Apache Web Server. Later in this system, teachers can find a variety of information related to student attendance. The results of this study indicate that by using this system can save time when making process, and Presence. In addition, students are also no longer be able to commit fraud related to student attendance.